Down‐regulated long non‐coding RNA ANRIL restores the learning and memory abilities and rescues hippocampal pyramidal neurons from apoptosis in streptozotocin‐induced diabetic rats via the NF‐κB signaling pathway - Wen, Xin; Han, Xin‐Rui; Wang, Yong‐Jian; Wang, Shan; Shen, Min; Zhang, Zi‐Feng; Fan, Shao‐Hua; Shan, Qun; Wang, Liang; Li, Meng‐Qiu; Hu, Bin; Sun, Chun‐Hui; et al. (Journal of cellular biochemistry, 2018)
Diabetes often causes learning and memory deficits, which leads to unfavorable behavioral performance. In this study, we investigated the effects of long non‐coding RNA (lncRNA) ANRIL on learning, memory abilities, and hippocampal neuronal apoptosis via the NF‐κB signaling pathway in streptozotocin (STZ)‐induced diabetic rats. After successful establishment of diabetic rat models, the subjects were then assigned into the DM, DM + si‐ANRIL, DM + si‐negative control (si‐NC) groups, as well as an additional normal group. Morris water maze test was employed to assess behavioral performance of rats, followed by the recording of body weight and blood glucose levels. Expressions of ANRIL, NF‐κB signaling pathway‐related, and apoptosis‐related genes were examined by qRT‐PCR and western blotting. Rat hippocampus expression levels of cleaved‐caspase‐3 were determined by immunofluorescence. Cell apoptosis was examined by TUNEL assay. Versus to the normal group, revealed there to be activation of the NF‐κB signaling pathway, decreased weight, increased blood glucose, increased escape latency, reduced residence time, memory impairment, increased cleaved‐caspase‐3 expression, and increased apoptosis were detected in the DM and DM + si‐NC groups. The DM + si‐ANRIL group exhibited inhibited NF‐κB signaling pathway, weight loss, decreased blood glucose, recovered memory, decreased cleaved‐caspase‐3 expression and reduced apoptosis compared to the DM group, with higher weight of rats, lower blood glucose levels, and stronger memory abilities in the DM + si‐ANRIL group. Taken together, these findings indicate that silencing lncRNA ANRIL promotes memory recovery and decreases hippocampal neurons apoptosis in diabetic rats through the inhibition of the NF‐κB signaling pathway. Silencing lncRNA ANRIL promotes memory recovery and decreases hippocampal neurons apoptosis in diabetic rats through the inhibition of the NF‐κB signaling pathway.